Patrimônio cultural: a indissociabilidade do patrimônio material e imaterial na cidade de Pombal/PB - Farias, Taise Costa de (2011)
The present report is about the cultural patrimony seen from a wider conception, not centered on the values of certain objects but on the relationship of the society with its culture, corroborating the idea of indissociability of the material and immaterial patrimony, through a study that relates Nossa Senhora do Rosário dos Pretos Church with its material value proved by its history and 18th century architecture and Rosário festival with its symbolic, cultural and popular universes as elements that form the cultural patrimony of Pombal city, on Upper Paraiba Hinterland. As research assumptions there is an idea of cultural patrimony as a process of collective identification on which the representation and the social-cultural values are fundamental on the investigation process of the existing bonds between population and the material and immaterial patrimony, Nossa Senhora do Rosário dos Pretos Church and Rosário festival, respectively. To this, the social representations theory was used as theoretical and methodological basis, which allows reaching the symbolic aspects and the imaginary aspects related to the urban area. For data collecting, four well distributed interviews were applied among the groups: IPAHEP historic heritage perimeter dwellers, members of the brotherhood and cultural groups, people linked to Nossa Senhora do Rosário dos Pretos Church and key people. On the information analysis, qualitative approaches were used, from the content analysis, in which the relation of the subject with patrimonial goods; links among appropriation, memory and place; the patrimonial goods which are firmer linked to the imaginary of population; and the values that structures the representations. This report tries to contribute to the study of subjective dimension of cultural patrimony specific related with the indissociability of the patrimony and the preservation of a collection of material and immaterial realizations of a society, which connected to a collective identity feeling contemplate the cultural patrimony of Pombal city on Paraíba.